Overcoming Addictions, a Web-Based Application, and SMART Recovery, an Online and In-Person Mutual Help Group for Problem Drinkers, Part 1: Three-Month Outcomes of a Randomized Controlled Trial - Hester, Reid K; Lenberg, Kathryn L; Campbell, William; Delaney, Harold D (JMIR Publications, 2013)
BackgroundOvercoming Addictions (OA) is an abstinence-oriented, cognitive behavioral, Web application based on the program of SMART Recovery. SMART Recovery is an organization that has adapted empirically supported treatment strategies for use in a mutual help framework with in-person meetings, online meetings, a forum, and other resources. ObjectiveTo evaluate the effectiveness of OA and SMART Recovery (SR) with problem drinkers who were new to SMART Recovery. Our experimental hypotheses were: (1) all groups will reduce their drinking and alcohol/drug-related consequences at follow-up compared to their baseline levels, (2) the OA condition will reduce their drinking and alcohol/drug-related consequences more than the control group (SR), and (3) the OA+SR condition will reduce their drinking and alcohol/drug-related consequences more than the control group (SR only). MethodsWe recruited 189 heavy problem drinkers primarily through SMART Recovery's website and in-person meetings throughout the United States. We randomly assigned participants to (1) OA alone, (2) OA+attend SMART Recovery (SR) meetings (OA+SR), or (3) attend SR only. Baseline and follow-ups were conducted via GoToMeeting sessions with a Research Assistant (RA) and the study participant. We interviewed significant others to corroborate the participant's self-report. Primary outcome measures included percent days abstinent (PDA), mean drinks per drinking day (DDD), and alcohol/drug-related consequences. ResultsThe intent-to-treat analysis of the 3-month outcomes supported the first hypothesis but not the others. Participants in all groups significantly increased their percent days abstinent from 44% to 72% (P<.001), decreased their mean drinks per drinking day from 8.0 to 4.6 (P<.001), and decreased their alcohol/drug-related problems (P<.001). Actual use relationships were found for the OA groups, between SR online meetings and improvement in PDA (r=.261, P=.033). In addition in the OA groups, the number of total sessions of support (including SR & other meetings, counselor visits) was significantly related to PDA (r=.306, P=012) and amount of improvement in alcohol-related problems (r=.305, P=.012). In the SR only group, the number of face-to-face meetings was significantly related to all three dependent variables, and predicted increased PDA (r=.358, P=.003), fewer mean DDD (r=-.250, P=.039), and fewer alcohol-related problems (r=-.244, P=.045), as well as to the amount of improvement in all three of these variables. Six-month follow-ups have been completed, and the results are currently being analyzed. ConclusionsThese results support our first experimental hypothesis but not the second or third. All groups significantly increased their PDA and decreased both their mean DDD and their alcohol-related problems, which indicates that both interventions being investigated were equally effective in helping people recover from their problem drinking. Trial RegistrationClinicaltrials.gov NCT01389297; http://clinicaltrials.gov/ct2/show/NCT01389297 (Archived by WebCite at http://www.webcitation.org/6Hh5JC7Yw).